Chemical composition and quality traits of Chinese chestnuts (Castanea mollissima) produced in different ecological regions. (1st September 2015) - Yang, Fang; Liu, Qi; Pan, Siyi; Xu, Can; Xiong, Youling L.
Abstract: The aim of this research was to study the chemical composition and processing adaptability of Chinese chestnuts grown in ten different ecological regions. Results, based on the harvest season 2012, showed that geographic locations significantly influenced the nutritional contents and quality traits of Chinese chestnuts. Chestnuts from the central region of China (such as Hubei province) had higher carbohydrate contents than from other regions, those from Guangdong province (deep south) had the highest protein content, and those from Hunan province (south) had the lowest fat content. Moreover, chestnuts from Zhejiang province (south) had the highest polyphenol content and those from Hunan province had the highest flavonoid content. Owing to their high sugar content, Hunan chestnuts were the sweetest. However, principal component analysis indicated that factors other than geographic regions also contributed to compositional and quality variations, indicating the necessity for further investigations.